DEVELOPMENT OF BIOPROCESSES FOR PRODUCTION AND PURIFICATION OF L-ASPARAGINASE FROM STAPHYLLOCOCCUS AUREUS, AND IN VITRO EFFECACY AGAINST HUMAN BREAST CNCER CELL LINE - T. J. Hassan,; S. I. Hussein, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2022)
The present study was aimed to isolate the abundant Staphylococcus aureus produce asparaginase and evaluate the efficacy of purified L-ASNase against a breast cancer cell line. From one hundred local isolates of S. aureus which subjected to the primary screening processes for asparaginase production, thirty-seven isolates with maximum ability of hydrolysis zone in primary screening (the ratio of Z more than 10 mm) were selected for secondary screening. It has been indicated that S. aureus TG98 had the highest productivity of the enzyme (255.8 U/mg protein). The highest producing-isolate was identified according to vitek test. The optimal conditions for ASNase production by the selected isolate was performed using submerged fermentation, where the medium (5) was utilized as the best medium for production, lactose as the best carbon source, NH4Cl as the best nitrogen source, pH 8 at 37 °C after 24 hr of incubation period, the specific activity was reached to 496.99 U/mg. The enzyme was purified by gel filtration chromatography utilizing Sephadex G-150. The results indicated that there is an elevating in final purification folds 2 time with 103% yield of enzyme. Also, it was exhibited maximal activity and stability at pH 8.0.  Also it was active and stable at 37°C.The highest rate of enzyme specificity found with asparagine. The breast tumor cells proliferation was significantly suppressed by the cytotoxic effect of L-ASNase comparison with normal cell line (WRL-68).